Multidrug resistance in the standardized treatment of colon cancer harboring a rare fibrosarcoma B-type (BRAF) p.N581I mutation: a case report - Wang, Xiaoyan; Zhao, Chenyi; Gong, Yang; Wang, Ying; Guo, Feng (Frontiers in Oncology, 2023)
BRAF non-V600 mutations are a distinct molecular subset of colorectal cancer (CRC) that has little to no clinical similarity to the BRAF V600 mutation. It is generally considered that the BRAF non-V600 mutations correlate with better survival of CRC patients. In this report, we present an unusual case that a midlife female patient who was initially diagnosed with stage IIIC colon cancer and multiple metastases were found 25 months after radical surgery. Next-generation sequencing (NGS) revealed the BRAF p.N581I (c.1742A>T) mutation. She received chemotherapy, targeted therapy, and immunotherapy. However, the disease progressed rapidly with rare metastasis of bone and cerebellum. This case highlights that the BRAF non-V600 mutations, such as BRAF p.N581I mutant, may lead resist to epidermal growth factor receptor (EGFR) inhibitors and result in a rapid course in colorectal cancer. The role of BRAF p.N581I mutation in colorectal cancer demands more attention.